Association of bacteria and viruses with wheezy episodes in young children: prospective birth cohort study. (4th October 2010) - Bisgaard, Hans; Hermansen, Mette Northman; Bønnelykke, Klaus; Stokholm, Jakob; Baty, Florent; Skytt, Nanna Lassen; Aniscenko, Julia; Kebadze, Tatiana; Johnston, Sebastian L
Abstract : Objective To study the association between wheezy symptoms in young children and the presence of bacteria in the airways. Design Birth cohort study. Setting Clinical research unit in Copenhagen. Participants Children of asthmatic mothers, from age 4 weeks to 3 years, with planned visits and acute admissions to the research clinic. Main outcome measure Frequency of bacteria and virus carriage in airway aspirates during wheezy episodes and at planned visits without respiratory symptoms. Results 984 samples (361 children) were analysed for bacteria, 844 (299 children) for viruses, and 696 (277 children) for both viruses and bacteria. Wheezy episodes were associated with both bacterial infection (odds ratio 2.9, 95% confidence interval 1.9 to 4.3; P<0.001) and virus infection (2.8, 1.7 to 4.4; P<0.001). The associations of bacteria and viruses were independent of each other. Conclusion Acute wheezy episodes in young children were significantly associated with bacterial infections similar to but independent of the association with virus infections.